Genetic evidence against involvement of TRPC proteins in SOCE, ROCE, and CRAC channel function - Susperreguy, Sebastian (2024)
Using genetically engineered mice andcell lines derived from genetically engineered mice we show that depletion ofER delimited Ca2+ stores activate heteromeric Ca2+ entry (SOCE)channels formed obligatorily, but not exclusively by Orai1 molecules.Comparison of Orai dependent Ca2+ entries revealed Orai1 to bedominant when compared to Orai2 and Orai3. Unexpectedly, we found that storedepletion activated Ca2+ entry does not depend obligatorily on functionallyintact TRPC molecules, as SOCE monitored with the Fura2 Ca2+reporter dye is unaffected in cells in which all seven TRPC coding genes havebeen structurally and functionally inactivated. Unexpectedly as well, we foundthat TRPC-independent Gq-coupled receptor operated Ca2+ entry (ROCE)also depends on Orai1. Biophysical measurements of Ca2+ releaseactivated Ca2+ currents (Icrac) are likewise unaffected by ablationof all seven TRPC genes. We refer to mice and cells carrying the seven-fold disruptionof TRPC genes as TRPC heptaKO mice and cells. TRPC heptaKO mice are fertile allowingthe creation of a new homozygous inbred strain.